Reversible Polymorphic Transition and Hysteresis‐Driven Phase Selectivity in Single‐Crystalline C8‐BTBT Rods. Issue 3 (20th December 2019) - Kim, Min‐Woo; Kwon, Sooncheol; Kim, Jehan; Lee, Changhoon; Park, Ina; Shim, Ji Hoon; Jeong, Il‐Seok; Jo, Yong‐Ryun; Park, Byoungwook; Lee, Joo‐Hyung; Lee, Kwanghee; Kim, Bong‐Joong
Abstract: Organic semiconductors (OSCs) are highly susceptible to the formation of metastable polymorphs that are often transformed by external stimuli. However, thermally reversible transformations in OSCs with stability have not been achieved due to weak van der Waals forces, and poor phase homogeneity and crystallinity. Here, a polymorph of a single crystalline 2, 7‐dioctyl[1] benzothieno[3, 2‐b][1]benzothio‐phene rod on a low molecular weight poly(methyl methacrylate) (≈120k) that limits crystal coarsening during solvent vapor annealing is fabricated. Molecules in the polymorph lie down slightly toward the substrate compared to the equilibrium state, inducing an order of greater resistivity. During thermal cycling, the polymorph exhibits a reversible change in resistivity by 5.5 orders with hysteresis; this transition is stable toward bias and thermal cycling. Remarkably, varying cycling temperatures leads to diverse resistivities near room temperature, important for nonvolatile multivalue memories. These trends persist in the carrier mobility and on/off ratio of the polymorph field‐effect transistor. A combination of in situ grazing incident wide angle X‐ray scattering analyses, visualization for electronic and structural analysis simulations, and density functional theory calculations reveals that molecular tilt governs the charge transport characteristics; the polymorph transforms as molecules tilt, and thereby, only a homogeneous single‐crystalline phase appears at each temperature. Abstract : A polymorph of a single crystalline 2, 7‐dioctyl[1] benzothieno[3, 2‐b][1]benzothio‐phene rod, synthesized on a low molecular weight poly(methyl methacrylate) exhibits a reversible change in resistivity by 5.5 orders with hysteresis during thermal cycling. Varying cycling temperatures lead to diverse resistivities near room temperature, important for nonvolatile multivalue memories. The polymorph transforms as molecules tilt and thus, only a homogeneous single‐crystalline phase appears at each temperature.